Pembuatan dan Pengujian Kondisioner Rambut Menggunakan Lendir dari Daun Kembang Sepatu (Hibiscus rosa-sinensis L.) - Hamidah Supriati; Irham Pratama Ridwan (Fakultas Farmasi Universitas Pancasila, 2019)
Many ornamental plant growing in tropical and subtropical regions one is Hibiscus which is a native plant from East Asia. Conditioner is one of semi solid preparation used to hair after using shampoo. The porpose of the research is getting formulation hair conditioner from Hibiscus with various concentration. This research is a descriptive analytic in the laboratory. Conditioner making with mix oil phase and melted water. The indrediens to be use are dimethicone, sethyl alcohol, stearic acid, TEA, glycerin, methyl paraben, propyl paraben and aquadest. Physical stability tests carried out were organoleptic test, homogeneity test, pH test and cream type test with various concentrations of hibiscus leaf mucus which were 15%, 20%, 25% and 30%, and as a comparison were the formulations of conditioner preparations without using hibiscus mucus . The results showed that the manufacture of conditioner with variations in the concentration of mucilage of hibiscus leaves (Hibiscus rosa-sinensis L.) and physical stability testing on formula 4 shows stable and softer textured results. The conclusion obtained is that formulas 1, 2, 3 and 4 have met the requirements of semi-solid preparations.